Spillover Effects of Sanctions on Airlines - Corbet, S.; Nicolau, J.L.; Oxley, Leslie (2025)
To counter the escalating threat of direct conflict with rogue nations, the use of sanctions packages has become a preferred tactical response. However, although targeted, there are significantly elevated spillover effects that can generate sectoral damage. While the literature on sanctions has focused on analyzing the effectiveness and the impact on the sanctioned and sanctioning country, spillover effects have not been addressed in the tourism and travel industry. Based on behavioral decision theory and modern portfolio theory, this study states hypotheses and confronts two potential results derived from each theory regarding the way negative consequences of sanctions spill over into airlines. Using the aviation sanctions packages derived from the Russia-Ukraine war in 2022 in different regions worldwide, the results indicate greater spillovers flow into airlines than other aviation-related corporations, into big firms than small firms, and with significant differential effects on each analyzed region.